2016
DOI: 10.1093/mnrasl/slw183
|View full text |Cite
|
Sign up to set email alerts
|

ALMA observations of the supergiant B[e] star Wd1-9

Abstract: Mass-loss in massive stars plays a critical role in their evolution, although the precise mechanism(s) responsible -radiatively driven winds, impulsive ejection and/or binary interaction -remain uncertain. In this paper we present ALMA line and continuum observations of the supergiant B[e] star Wd1-9, a massive post-Main Sequence object located within the starburst cluster Westerlund 1. We find it to be one of the brightest stellar point sources in the sky at millimetre wavelengths, with (serendipitously ident… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…Recently, the LHA 120-S 35 membership to the cluster SL 482 has been discussed by Bitsakis et al (2017), who were able to determine the members of the star cluster using a robust decontamination technique, providing a probability of more than 92% that LHA 120-S 35 is member of the cluster. The previously reported B[e]SGs associated to open clusters are: LHA 120-S 111, which belongs to the compact cluster NGC 1994 of the LMC (Melgarejo et al 2001;Lortet & Testor 1988) and Wd1-9, which is a member of the massive Galactic stellar cluster Westerlund 1 (Clark et al 2013b;Fenech et al 2017). The small number of B[e]SGs found in stellar clusters is reasonable taking into account that their lifetime in this post-main-sequence phase is relatively short.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Recently, the LHA 120-S 35 membership to the cluster SL 482 has been discussed by Bitsakis et al (2017), who were able to determine the members of the star cluster using a robust decontamination technique, providing a probability of more than 92% that LHA 120-S 35 is member of the cluster. The previously reported B[e]SGs associated to open clusters are: LHA 120-S 111, which belongs to the compact cluster NGC 1994 of the LMC (Melgarejo et al 2001;Lortet & Testor 1988) and Wd1-9, which is a member of the massive Galactic stellar cluster Westerlund 1 (Clark et al 2013b;Fenech et al 2017). The small number of B[e]SGs found in stellar clusters is reasonable taking into account that their lifetime in this post-main-sequence phase is relatively short.…”
Section: Discussionmentioning
confidence: 72%
“…A similar global structure composed by an equatorial disc perpendicular to a bipolar flow has been proposed to interpret the observations at millimeter and radio wavelengths for the B[e]SGs MWC 349 (Danchi et al 2001; Table 1). Tafoya et al 2004) and Wd1-9 (Fenech et al 2017) and the optical and infrared observations of MWC 137 .…”
Section: Discussionmentioning
confidence: 94%
“…Lastly, while X-ray observations and our RV studies suggest that a number of (colliding wind) binaries are found within the cluster (Wang et al 2006, Papers II and III), the Arches appears to lack any systems in which rapid case-A mass-transfer is ongoing. Several examples of such systems have been proposed -Wd1-9 (Clark et al 2013b;Fenech et al 2017), RY Scuti (Gehrz et al 1995(Gehrz et al , 2001Grundstrom et al 2007), NaSt1 (Mauerhan et al 2015), and LHA 115-S 18 (Clark et al 2013a) -and appear to manifest as (supergiant) B[e] stars (cf. discussion in Kastner et al 2010), supporting a combination of a rich low excitation emission line spectrum and bright X-ray, IR, and sub-mm/radio continuum emission (due to colliding winds, the presence of hot dust and a highly elevated mass-loss rate, respectively).…”
Section: The Absence Of H-free Wrs Lbvs and Interacting Binariesmentioning
confidence: 99%
“…Ritchie et al 2009aRitchie et al , 2010 have revealed a rich binary population comprising pre-interaction (e.g. Wd1-43a; Ritchie et al 2011), interacting (Wd1-9;Clark et al 2013, Fenech et al 2017) and post-interaction binaries (Wd1-13 and -239; Ritchie et al 2010.…”
Section: The Ymc Westerlundmentioning
confidence: 99%